A 3-kyr plateau of middle Holocene higher sea levels on the central Kanto Plain, Japan. (1st November 2022) - Tanabe, Susumu
Abstract: Middle Holocene higher sea levels during 7–4 ka in Asia, Australia, and South America varied in duration and stability. Abundant archaeological excavations have been carried out in the Tokyo urban area, which is situated on the alluvial and coastal lowlands of the central Kanto Plain. In this study, 74 sea-level index points and 241 limiting data points were compiled from Japanese scientific papers and excavation reports for 109 locations on the central Kanto Plain. These data suggest that the relative mean sea level changed from −4 ± 1.5 m at 8 ka to 3 ± 1.5 m during 7–4 ka, to −1.5 ± 1 m at 3 ka, and then to 0 ± 1 m during 2–0 ka. During the 7–4-ka sea-level plateau on the central Kanto Plain, the sea level did not fluctuate. The height distribution at 52 locations on the central Kanto Plain shows that sea level remained stable for 3 kyr, with no local differences in the duration, in an area of 90 km × 90 km. The temporary sea-level drop at 3 ka corresponds to the "Yayoi regression", which has been previously reported on the central Kanto Plain, although its driving mechanism is unknown. Crustal deformation can be neglected as less important than the spring tidal range, which was ca. 3 m at 7 ka on the central Kanto Plain. By using a dense dataset to confirm the occurrence of a middle Holocene higher sea-level plateau on the central Kanto Plain, this study strongly suggests that glacier melting occurred two steps, at 7 ka and 4 ka. Highlights: Mean sea level plateaued at 3.0 m during 7–4 ka and mean high water springs was 4.5 m. Middle Holocene higher sea levels varied locally depending on channel erosion. Mean sea level temporarily dropped to −1.5 m at 3 ka. Local crustal deformation is roughly the same at scales of 100 kyr and several kyr. Shell midden locations and ages relate to tidal-flat development and sea-level change.